Raw Denim as a Means of Communication: Self Expression and Identity - Fadhli Rahmandani; Ratna Permata Sari (Asian Journal of Media and Communication, 2020)
Fashion plays an important role in the self-identity formation processes. In this sense, jeans are getting increasingly popular as it has become a trend in fashion. This study examines how raw denim becomes a form of self-expression for its wearer. Applying a qualitative approach, this study has gathered the empirical data through in-depth interviews and observations to an Indonesian denim community called as INDIGO. This study shows that raw denim users have several ways to express themselves as raw denim users. Denim has characteristics that allow for personalization according to one’s body shape, especially the creases and fades that mark the daily habits of the wearer. Denim becomes a representation of the wearers and a way to express their self identity. In order to show that they are a denimhead, one must consider every related actions they take in using raw denim, including joining in a denim community. Keywords: denim, fashion, self expression, identity, Indonesian denim community.